Implementasi Rapid Application Development Pada Pengembangan E-Commerce Persambi Karawang - Saepudin, Atang; Tunjung Kusumo, Aryo; Rudianto, Biktra (PROFITABILITAS, 2023)
Advances in computer technology today have moved quickly and massively in various aspects. The computer, which is equipment created to facilitate human work, has changed the way and work system from conventional to computerized. Computerization has now been applied in all fields, including the product sales business. One of them is Pengcab Persambi Karawang which also requires an information system that can support and provide satisfactory service for customers in selling their products. For this reason, researchers built a sales system at the Persambi Karawang Branch Office, which until now has not been computerized. The existing system at Pengcab Persambi Karawang is still done manually, starting from recording customers who buy products, to storing other data related to the sales process to making reports, so that it is possible during the process that errors occur in the recording. The inaccuracy of the reports that are made and the delay in finding the necessary data are the weaknesses of the current system. The design of this information system is the best solution to solve the problems that exist in this company, and with a computerized system an effective and efficient activity can be achieved in supporting the activities of this organization. A computerized system is better than a manual system so that it runs more effectively and efficiently and the current sales system is more conducive than the previous system. The e-commerce system development method is carried out using the Rapid Application Development method approach. This method is a system development method that is carried out quickly and briefly. So it is considered more appropriate in the development of e-commerce systems.